2018
DOI: 10.5551/jat.42812
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Glomerular Filtration Rate Estimated on Admission and Acute Stroke Outcome: The Shiga Stroke Registry

Abstract: Aim: Although renal dysfunction has been identified as a novel risk factor affecting stroke prognosis, few have analyzed the association within large-scale population-based setting, using wide-range estimated glomerular filtration rate (eGFR) category. We aimed to determine the association of admission eGFR with acute stroke outcomes using data from a registry established in Shiga Prefecture, Japan.Methods: Following exclusion of patients younger than 18 years, with missing serum creatinine data, and with onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…CKD is an independent risk factor of cardiovascular disease [3]. For stroke patients, some studies suggested that CKD with decreased estimated glomerular filtration rate (eGFR) significantly increased the risk of stroke mortality [4,5]. In intravenous thrombolysis (IVT) therapy, one study with large sample size revealed that low GFR was independently associated with poor outcome and the risk of symptomatic intracerebral hemorrhage (sICH) [6].…”
Section: Introductionmentioning
confidence: 99%
“…CKD is an independent risk factor of cardiovascular disease [3]. For stroke patients, some studies suggested that CKD with decreased estimated glomerular filtration rate (eGFR) significantly increased the risk of stroke mortality [4,5]. In intravenous thrombolysis (IVT) therapy, one study with large sample size revealed that low GFR was independently associated with poor outcome and the risk of symptomatic intracerebral hemorrhage (sICH) [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study, 2,308 Chinese subjects with an eGFR of 60-89 and 30-59 tended to have more cardiovascular risk factors and a higher prevalence of CVD than individuals with an eGFR 90 4) . An analysis of 2,813 patients with acute stroke indicated the significant association between reduced renal function and hospital death, in which adjusted odds ratios and 95% CIs for in-hospital death were 1.54 (1.04-2.27) when the eGFR 45, 1.07 (0.72-1.58) when the eGFR was 45-59, and 1.04 (0.67-1.59) when the eGFR ≥ 90 5) . In a 4.6-year longitudinal observation of 70 asymptomatic Japanese participants without CKD, median values of coronary artery calcium score and abdominal aortic calcification index increased from 40.2 to 113.3 and from 13.2% to 21.7%, respectively 6) .…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies have some limitations. The cross-sectional study design limits the ability to identify the causative relationship between factors 4,5,7) , and the small number of study subjects has the weakness in generalizing the findings 6) . In contrast, we monitored the incident IHD for an average follow-up period of 4.35 0.55 years based on the ICD code of IHD registered in hospitals where patients were actually treated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations